Persepsi Dan Ekspektasi Pelanggan Terhadap Kualitas Layanan Kereta Bandara Soekarno-Hatta - Handoko, Handoko; Rozaq, Fadli (Politeknik Perkeretaapian Indonesia Madiun, 2018)
The research objective is to determine customer perceptions and expectations of the Soekarno-Hatta Airport train service. Analysis of customer perceptions and expectations is used to find out the services desired, needed, and expected by passengers so as to create customer satisfaction. This research is a type of descriptive research using a quantitative approach. The study population is all passengers of the Soekarno-Hatta airport train. The sampling technique used is quota sampling technique. Research instruments using questionnaires and research data analysis using gap analysis and descriptive analysis. The results of this study are there are 4 dimensions that are considered unsatisfactory customers, namely the dimensions of physical evidence, responsiveness, reliability, and guarantees, and there are 1 service dimensions that are considered satisfactory customers, namely the empathy dimension